Research on Characteristic of Hydrodynamic Bearing with the Surface Micro-pit - Shaolin Zhang; Lingxue Li; Boqian Xia (Jixie chuandong)
Taking the hydrodynamic bearing with surface micro-pits as the research object， a mathematical model of oil film characteristics is established based on the flow balance of the micro-pits， and the static and dynamic characteristics and stability parameters of the bearing are obtained with the depth and area of the micro-pits. The changes in the rate， shape and arrangement of the bearing are compared with the calculation results of the bearing characteristics of the smooth bearing surface. The results show that the pit shape， distribution， size and other factors significantly affect the oil film bearing capacity， flow rate， attitude angle， average temperature rise and other static characteristic parameters and stiffness， damping and other dynamic characteristic parameters. Among them， the optimal micro-pit depth makes the oil film bearing load capacity has been increased by 15.3%， and the threshold rotary speed has been increased by 6.9%. This research has reference significance for the study of hydrodynamic bearings with surface micro-pits.